1986
DOI: 10.1002/oms.1210210106
|View full text |Cite
|
Sign up to set email alerts
|

Electron impact and chemical ionization mass spectra of some tetra‐acetylated anomeric glycosides

Abstract: Electron impact and chemical ionization (CH,, iso-C,H,, and NH,) mass spectra of some tetra-acetylated anomeric glycosides have been examined with a view to the characterization of anomeric pairs. Minor differences observed in the relative intensities of common ions in the anomeric pairs in the electron impact mass spectra are found to be enhanced in the methane and isobutane chemical ionization mass spectra. In the absence of thermal decomposition, the p-anomers show greater ion abundances of common glycosyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 10 publications
3
6
0
Order By: Relevance
“…H]+ ions could be attributed to their chelate structure. 12 As expected, no sugar peaks appeared in the spectra of flavone mono-C-glycosides (Table 3), while, in the case of the C-diglycoside 21, terminal sugar ions were produced and consecutive water elimination occurred (Table 4).…”
Section: ( M / Z (O/orelint))supporting
confidence: 56%
“…H]+ ions could be attributed to their chelate structure. 12 As expected, no sugar peaks appeared in the spectra of flavone mono-C-glycosides (Table 3), while, in the case of the C-diglycoside 21, terminal sugar ions were produced and consecutive water elimination occurred (Table 4).…”
Section: ( M / Z (O/orelint))supporting
confidence: 56%
“…21 The authors attribute this to the higher stability of the˛anomer due to the anomeric effect. A study of tetraacetylated anomeric glucosides and galactosides that were measured under EI and various CI conditions 19 also shows the higher abundances of oxonium ions in some of theˇ-glucose anomers when compared with the˛-isomers. It has also been reported that acetic acid loss is enhanced by the presence of a neighboring acyloxy group in a trans configuration of cyclohexyl-based systems that are not carbohydrates.…”
Section: All Six Isomers Produce High Intensities Of [M C Nh 4 ]mentioning
confidence: 98%
“…Its JR and 1H-NMR spectra agree with the published values (16), the coupling constants having now been analysed in detail. The CI mass spectrum provided the [M + NH4P; the El does not give the molecular ion but shows peaks at m/z 331 from the tetraacetate of fl-nglucopyranose (17) and at m/z 396 and 255 from the sterol (18). The assignments for 2a are based on literature values for /3-sitosterol (19) (where C-24 seems to be in error by about 5 ppm), its acetate (20) and the glucose residue of sucrose octaacetate (21) as well as the published chemical shifts for sitosterol-3-O-stearoyl-fl-n-glucopyranoside taking into account the multiplicities (where no assignments were made) (22).…”
mentioning
confidence: 99%